MANAJEMEN LIMBAH MAKANAN BERBASIS BLOCKCHAIN DENGAN INTEGRITAS SHA- 256 UNTUK MENDUKUNG KEBERLANJUTAN - Evan, Felicia; Madyatmadja, Evaristus Didik (ISTEK WIDURI, 2025)
Indonesia ranks fourth globally in food waste generation, addressing this significant issue, this paper explores the integration of blockchain technology with SHA-256 hashing to enhance food waste management practices in the restaurant industry. The proposed system leverages the immutable and transparent nature of blockchain to ensure accurate tracking, enhanced transparency, and accountability throughout the food waste lifecycle. By utilizing smart contracts, the system automates compliance and enforces waste management protocols, leading to more efficient operations and significant reductions in food waste. Empirical evaluations in real-world settings suggest that this blockchain-driven approach not only promotes sustainability but also provides economic benefits by optimizing resource utilization and reducing operational costs. Further research is recommended to address scalability, cost implications, and data privacy concerns to ensure the system's broader applicability and effectiveness.